2021
DOI: 10.1039/d1cp01985f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of base analogue modified nucleic acids by force spectroscopy

Abstract: We use mechanical unfolding of single DNA hairpins with modified bases to accurately assess intra- and intermolecular forces in nucleic acids. As expected, the modification stabilizes the hybridized hairpin, but...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In a recent study, we showed that the tC BA can stabilize a fully complementary DNA hairpin. 35 Here we demonstrate how BAs can be used in optical tweezers experiments to explore conformational states of RNA structures and transitions between them. Since BAs are similar in size to natural bases and typically designed to (1) maintain specificity for complementary bases; (2) restore hydrogen bonds with their complements; and/or (3) preserve the intrinsic secondary structure of nucleic acids, their incorporation into an RNA/DNA of interest enables studies of a selected region within the molecule with base-pair resolution.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In a recent study, we showed that the tC BA can stabilize a fully complementary DNA hairpin. 35 Here we demonstrate how BAs can be used in optical tweezers experiments to explore conformational states of RNA structures and transitions between them. Since BAs are similar in size to natural bases and typically designed to (1) maintain specificity for complementary bases; (2) restore hydrogen bonds with their complements; and/or (3) preserve the intrinsic secondary structure of nucleic acids, their incorporation into an RNA/DNA of interest enables studies of a selected region within the molecule with base-pair resolution.…”
Section: Discussionmentioning
confidence: 97%
“…In our previous optical tweezers study using the tC BA in a fully complementary DNA hairpin, we observed an increase in the hairpin's mechanical stability with tC incorporation. 35 tC is chemically similar to tC O (ref. 34 ) and in UV melting studies, both tC O (ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These dsDNAs served as handles to attach the molecule to beads coated with streptavidin and anti-digoxigenin, respectively (Figure 1B). To the best of our knowledge, short DNA handles have never been used before in optical tweezers studies of RNA molecules, but merely in a few DNA-folding studies [25][26][27][28]. The advantage of using short DNA handles over the more common long handles (typically~500 bp-a few kbp) [18,[29][30][31][32][33] is that they improve signal-to-noise and make the force changes approximately linear with extension (Figure 1C), which significantly benefits the data analysis [25].…”
Section: Design Of the Pre-mirna-377 Construct For Optical Tweezers Studiesmentioning
confidence: 99%